Economic burden of atopic dermatitis in Portugal - Cunha, Ana Soraia (2025)
Cunha, A. S., Victorino, G., Silva, J. M. E., & Coelho, P. S. (2025). Economic burden of atopic dermatitis in Portugal: a cross-sectional study. Scientific Reports, 15, 1-10. Article 7717. https://doi.org/10.1038/s41598-025-91896-y --- The study was conducted with the support SPDV and ADERMAP and was funded by Sanofi. This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project UIDB/04152/2020 (DOI: https://doi.org/10.54499/UIDB/04152/2020) - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.